Truck Triangulation as a Strategic Response to Delivery Inefficiencies in Export-Import Operations: A Case Study of a Global Logistics Company in Jakarta - Agustina, Indri; Purwanto, Agustinus Hariadi Djoko (International Journal of Social and Management Studies, 2025)
Logistics inefficiencies, particularly in export-import operations, remain a persistent issue in emerging markets such as Indonesia, where infrastructure constraints and high port congestion exacerbate delivery delays and empty truck returns. Existing strategies often fail to address the combined challenges of route inefficiency, asset underutilization, and lead time variability. This study investigates the effectiveness of Truck Triangulation as a strategic logistics intervention to reduce delivery inefficiencies by optimizing truck routes and fleet utilization in the context of export-import operations at global logistics company in Jakarta. A mixed-methods approach was employed, combining qualitative insights from focus group discussions with logistics managers and operational staff, and quantitative performance data analyzed. The study compared key performance indicators before and after the implementation of truck triangulation, including lead time, fleet turnover, and operational cost. The findings validate Truck Triangulation as an effective, scalable logistics model for export-import operations in infrastructure-constrained markets. This research contributes to practice by demonstrating how lean routing strategies and digital coordination can drive logistics performance and sustainability in emerging economies.